PEMETAAN TAKSONOMI MAMALIA MELALUI PERSPEKTIF KEARIFAN LOKAL DI KEPULAUAN NIAS - Murnihati Sarumaha; Yuniati Halawa; Rikamawati Hulu; Lira Sari Balaki Laia; Okte R.T.M. Gowasa; Jhosep Edison Gowasa; Dastik Dao; Pansakti Laia; Trilis Debora Laia; Intan Bestarii Duha; Ekardiana Bohalima; Friska Tafonao; et al. (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Nias Archipelago, located on the western coast of Sumatra, has a rich biodiversity, including mammal species that play a crucial role in maintaining the balance of ecosystems. The people of Nias have long possessed profound knowledge of mammals through local wisdom passed down through generations. However, the mapping of mammalian taxonomy in this area is still limited. This community service activity aims to map the mammalian taxonomy of the Nias Archipelago by integrating scientific perspectives with the local wisdom of the community. Through a participatory approach, local people are involved in the identification of mammal species, recording local names, and understanding their habitats and behaviors. The results of this community service activity show that the people of Nias have extensive knowledge of the mammal species around them, which has not been fully documented in scientific studies. This approach not only enriches the mammalian taxonomy data in the Nias Archipelago but also raises community awareness of the importance of environmental conservation. The mapping results can serve as a basis for more effective conservation efforts by integrating traditional knowledge and scientific approaches to preserve biodiversity in the region.